ANALISIS FORMULASI KABIJAKAN RENCANA TATA RUANG WILAYAH (RTRW) DI KABUPATEN GORONTALO - Arlan Ahmad; Udin Hamim; Lisda Van Gobel (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
The delay in the enactment of the Regional Spatial Plan (RTRW) of Gorontalo Regency has the potential to hinder legal certainty in spatial utilization and impede sustainable regional development. This study aims to analyze the policy formulation process & identify the factors contributing to its delayed enactm ent. A descriptive qualitative approach was employed. Data were collected through in-depth interviews, observations, and docum ent analysis involving nine informants selected using purposive and snowball sampling techniques. Data were analyzed using the interactive model of Miles and Huber man. The findings indicate that the RTRW formulation process has followed the stages of document preparation, problem identification, public consultati on, & decision-making. However, implement ation remains subopt imal due to weak inter-agency coordination, complex institutional authority, limited human resource capacity, and political dynam ics. Strengthening coordination, harmonizing regulations, enhanc ing institutional capacity, & expanding inclusive publicion are ess ential for achieving & sustainable spatial planning governance.